Synthesis, Antifungal Activity, and 3D-QSAR Study of Novel Nopol-Derived 1,3,4-Thiadiazole-Thiourea Compounds - Ming Chen; Wen-Gui Duan; Gui-Shan Lin; Zhong-Tian Fan; Xiu Wang (Molecules, 2021)
A series of novel nopol derivatives bearing the 1,3,4-thiadiazole-thiourea moiety were designed and synthesized by multi-step reactions in search of potent natural product-based antifungal agents. Their structures were confirmed by FT-IR, NMR, ESI-MS, and elemental analysis. Antifungal activity of the target compounds was preliminarily evaluated by in vitro methods against Fusarium oxysporum f. sp. cucumerinum, Cercospora arachidicola, Physalospora piricola, Alternaria solani, Gibberella zeae, Rhizoeotnia solani, Bipolaris maydis, and Colleterichum orbicalare at 50 µg/mL. All the target compounds exhibited better antifungal activity against P. piricola, C. arachidicola, and A. solani. Compound 6j (R = m, p-Cl Ph) showed the best broad-spectrum antifungal activity against all the tested fungi. Compounds 6c (R = m-Me Ph), 6q (R = i-Pr), and 6i (R = p-Cl Ph) had inhibition rates of 86.1%, 86.1%, and 80.2%, respectively, against P. piricola, much better than that of the positive control chlorothalonil. Moreover, compounds 6h (R = m-Cl Ph) and 6n (R = o-CF3 Ph) held inhibition rates of 80.6% and 79.0% against C. arachidicola and G. zeae, respectively, much better than that of the commercial fungicide chlorothalonil. In order to design more effective antifungal compounds against A. solani, analysis of the three-dimensional quantitative structure–activity relationship (3D-QSAR) was carried out using the CoMFA method, and a reasonable and effective 3D-QSAR model (r2 = 0.992, q2 = 0.753) has been established. Furthermore, some intriguing structure–activity relationships were found and are discussed by theoretical calculation.